Bile Acids and Their Derivatives as Potential Modifiers of Drug Release and Pharmacokinetic Profiles - Nebojša Pavlović; Svetlana Goločorbin-Kon; Maja Ðanić; Bojan Stanimirov; Hani Al-Salami; Karmen Stankov; Momir Mikov (Frontiers Media S.A., 2018)
Bile acids have received considerable interest in the drug delivery research due to their peculiar physicochemical properties and biocompatibility. The main advantage of bile acids as drug absorption enhancers is their ability to act as both drug solubilizing and permeation-modifying agents. Therefore, bile acids may improve bioavailability of drugs whose absorption-limiting factors include either poor aqueous solubility or low membrane permeability. Besides, bile acids may withstand the gastrointestinal impediments and aid in the transporter-mediated absorption of physically complexed or chemically conjugated drug molecules. These biomolecules may increase the drug bioavailability also at submicellar levels by increasing the solubility and dissolution rate of non-polar drugs or through the partition into the membrane and increase of membrane fluidity and permeability. Most bile acid-induced effects are mediated by the nuclear receptors that activate transcriptional networks, which then affect the expression of a number of target genes, including those for membrane transport proteins, affecting the bioavailability of a number of drugs. Besides micellar solubilization, there are many other types of interactions between bile acids and drug molecules, which can influence the drug transport across the biological membranes. Most common drug-bile salt interaction is ion-pairing and the formed complexes may have either higher or lower polarity compared to the drug molecule itself. Furthermore, the hydroxyl and carboxyl groups of bile acids can be utilized for the covalent conjugation of drugs, which changes their physicochemical and pharmacokinetic properties. Bile acids can be utilized in the formulation of conventional dosage forms, but also of novel micellar, vesicular and polymer-based therapeutic systems. The availability of bile acids, along with their simple derivatization procedures, turn them into attractive building blocks for the design of novel pharmaceutical formulations and systems for the delivery of drugs, biomolecules and vaccines. Although toxic properties of hydrophobic bile acids have been described, their side effects are mostly produced when present in supraphysiological concentrations. Besides, minor structural modifications of natural bile acids may lead to the creation of bile acid derivatives with the reduced toxicity and preserved absorption-enhancing activity.